2003 IEEE Radiation Effects Data Workshop
DOI: 10.1109/redw.2003.1281366
|View full text |Cite
|
Sign up to set email alerts
|

Proton beam of variable energy - the new tool for investigation of radiation effects at PNPI synchrocyclotron

Abstract: A new variable energy (200 -1000 MeV) proton beam line at 1 GeV PNPI synchrocyclotron has been completed. The energy variation of the beam is provided by the copper degrader. Monte Carlo simulations of the beam propagation in the degrader as well as in the magneto-optics channel have been performed. Good agreement between theoretical calculations and experimental data is obtained. 0-7803-8127-0/03/$17.00 (C) 2003 IEEE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…To get 300-500 particles on the output of the beam channel, one has to simulate 10 6 particles after degrader that looks quite acceptable. Experimental studies showed good agreement with results of calculations of intensity, beam size, momentum spread and magnetic field in the dipoles and quadruples of the beam line [5].…”
Section: Design Of the Variable Energy Proton Beam Obtained By The Mosupporting
confidence: 73%
“…To get 300-500 particles on the output of the beam channel, one has to simulate 10 6 particles after degrader that looks quite acceptable. Experimental studies showed good agreement with results of calculations of intensity, beam size, momentum spread and magnetic field in the dipoles and quadruples of the beam line [5].…”
Section: Design Of the Variable Energy Proton Beam Obtained By The Mosupporting
confidence: 73%
“…The first one is availability of the new 200-900 MeV proton beams at PNPI 1 GeV synchrocyclotron [1]. Evaluation of LET spectra produced by such protons in bulk Si is an essential element of the experiment planning.…”
Section: Introductionmentioning
confidence: 99%
“…The experiment has been performed at 1-GeV PNPI synchrocyclotron. Since an external proton beam of the PNPI synchrocyclotron has a fixed energy of 1 GeV, in order to obtain proton beams with energies in the range from 200 to 900 MeV a method of energy decrease by the beam absorption in a copper degrader was applied [1]. The proton energy was measured by the time-of-flight method.…”
mentioning
confidence: 99%
“…The PPAC had a high efficiency for the fragment detection and good time characteristics (better than 300 ps time resolution for fission fragments). The latter property, together with the PPAC insensitivity to neutrons, photons and light charged particles with minimal energy loss in the matter, makes the PPACs extremely favorable tool for accelerator experiments, allowing one to place them in the direct proton beam, that provides the large solid angle for the fragment registration 1 .…”
mentioning
confidence: 99%